Respuesta :
Let's see
Let y=f(x)
- y=4x
Intechange x and y
- x=4y
Find y
- y=x/4
The inverse is y=x/4
Graphs attached
![Ver imagen Аноним](https://us-static.z-dn.net/files/dbe/6eabff077f41beadb4fa199b9151a315.jpg)
Answer:
[tex]\sf f^{-1}(x)=\dfrac{x}{4}[/tex]
Step-by-step explanation:
The inverse of a function is the reflection of the function in the line y = x
To find the inverse of a function:
Set the function to y:
⇒ y = 4x
Make x the subject:
[tex]\sf \implies x=\dfrac{y}{4}[/tex]
Change x to [tex]\sf f^{-1}(x)[/tex] and y to x:
[tex]\sf \implies f^{-1}(x)=\dfrac{x}{4}[/tex]
![Ver imagen semsee45](https://us-static.z-dn.net/files/d68/1316bfef0b3d882a9807fe08299f9a3a.png)